Phenotypic assessment of COPD using clinical, radiological, and functional parameters - Duygu Acar Karagül; Sevgi Behiye Saryal (Journal of Pulmonology and Intensive Care, 2026)
Aims: Chronic Obstructive Pulmonary Disease (COPD) is a heterogeneous condition with variable clinical presentation and disease progression. This study aimed to investigate the distribution of patients across defined COPD phenotypes and to compare their clinical, radiological, and functional characteristics. Methods: This cross-sectional descriptive study included 96 patients diagnosed with COPD. Patients were classified into four phenotype groups: asthma–COPD overlap syndrome (ACOS), non-exacerbator (NE), frequent exacerbator with emphysema (FEE), and frequent exacerbator with chronic bronchitis (FECB). Demographic, clinical, and pulmonary function parameters were analyzed and compared among groups. Forced expiratory volume in one second (FEV1), body mass index (BMI), COPD Assessment Test (CAT), diffusing capacity for carbon monoxide (DLCO), and inspiratory capacity/total lung capacity (IC/TLC) ratio were evaluated. Results: Of the patients, 83 (86.5%) were male and 13 (13.5%) were female, with a mean age of 65.22±7.85 years. The distribution of phenotypes was as follows: ACOS (9%), NE (53%), FEE (19%), and FECB (19%). The mean annual exacerbation rate was 1.27±1.2, and the mean FEV1 was 50.21±16.56%. The ACOS phenotype was characterized by a higher proportion of female patients, younger age, history of asthma and atopy, better clinical status, and relatively preserved lung function. In contrast, the FEE phenotype demonstrated a higher exacerbation frequency, poorer quality of life, and more severe airflow limitation. Patients in the FEE group had lower FEV1 and BMI, higher CAT scores, increased lung volumes and airway resistance, lower DLCO and partial pressure of oxygen (pO2), and an IC/TLC ratio below 25%. Conclusion: Distinct COPD phenotypes, particularly ACOS and FEE, exhibit significant differences in clinical and functional characteristics. Recognition of these phenotypes may help guide individualized management strategies, including pulmonary rehabilitation, nutritional support, and optimization of pharmacological and interventional treatments.